(untitled) (Research, Society and Development, 2021)
This study aims to seek evidence in the literature about the barriers faced by women living with HIV in the affective-sexual relationship. This is an integrative literature review, carried out by bibliographic survey in Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Database in Nursing (BDENF) and US National Library of Medicine National Institutes of health (PubMed) during the month of September 2020. Inclusion criteria were studies published in full from 2015 to 2020, in Portuguese and English that were freely available online. Duplicate articles, monographs, dissertations, thesis, reviews and those that did not correspond to the research objective were discarded. 2,090 articles were identified, but only 7 articles met the inclusion and exclusion criteria. Four (57.2%) were found in SciELO, two (28.6%) in BDENF and one (14.2%) in LILACS. This study allowed us to realize that the main obstacles faced by women living with HIV in the affective-sexual aspect are emotional, psychological and social, making noteworthy the different impacts that the diagnosis of HIV causes in women’s lives.